Ecological and genomic bases of urban environment adaptation in Anopheles gambiae and Anopheles coluzzii in Central Africa - (:unkn) unknown (My University, 2021)
The adaptation of species within the Anopheles gambiae complex to urban settings is of major interest for its potential implication in malaria transmission in cities in sub-Saharan Africa. This adaptation involves changes in their physiology, genetics and behavior, among others. During the last decades, a growing number of studies assessed Anopheles urban adaptation in Central Africa, but focused mainly on few cities located in forested areas. The objective of this thesis is to understand the evolution of Anopheles gambiae and Anopheles coluzzii populations in urban settings. To this end, we carried out an exhaustive larval sampling in four major cities of Central Africa: Libreville (Gabon), Douala (Cameroon), Brazzaville (Congo), and Bangui (CAR). We characterized the physical-chemical and ecological variables of 380 breeding sites and identified the presence of the different Anopheles species. Using an ecological modeling approach, we investigated the patterns of frequency variation of these Anopheles species within and across cities. Finally, we explored the genetic mechanisms associated with the presence of An. coluzzii in urban areas. Our study confirmed the capacity of An. gambiae and An. coluzzii to largely colonize Central Africa cities. Their presence across a variety of aquatic conditions revealed their environmental plasticity, a mirror of their ecological success in Africa. However, and despite their extensive presence in the four cities, these two species exhibit eco-geographical segregation. Environmental variables such as habitat, organic pollution, salinity, pH, presence or urban density, significantly influenced the frequency variation of urban larval habitats between An. coluzzii (predominant in coastal habitats) and An. gambiae (predominant in inland habitats). Despite the specific features of each city, we could predict the species frequency variation, revealing a common pattern in the adaptation to urban settings of both species in
Keywords: African Research